1998
DOI: 10.1109/55.735761
|View full text |Cite
|
Sign up to set email alerts
|

Improving low-temperature APCVD SiO2 passivation by rapid thermal annealing for Si devices

Abstract: The quality of low-temperature ( 400 C) atmospheric pressure chemical vapor deposited (APCVD) silicon dioxide (SiO 2 ) films has been improved by a short time rapid thermal annealing (RTA) step. The RTA step followed by a low temperature (400 C) forming gas anneal (FGA) results in a well-passivated Si-SiO 2 interface, comparable to thermally grown conventional oxides. Efficient and stable surface passivation is obtained by this technique on virgin silicon as well as on photovoltaic devices with diffused (n + +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The best values reported on low resistivity n-type substrates were in the 100-400 cm/ s range obtained on slightly higher resistivity substrates ͑3-6 ⍀͒, 12,13 and it is generally found that the effective surface recombination velocity decreases for increasing wafer resistivity. The surface recombination velocity shows only a limited injection level dependence, similar to what is observed for silicon carbide, amorphous silicon, and silicon nitride on low resistivity n-type crystalline silicon.…”
Section: A Surface Passivation By Sio 2 Filmsmentioning
confidence: 95%
See 4 more Smart Citations
“…The best values reported on low resistivity n-type substrates were in the 100-400 cm/ s range obtained on slightly higher resistivity substrates ͑3-6 ⍀͒, 12,13 and it is generally found that the effective surface recombination velocity decreases for increasing wafer resistivity. The surface recombination velocity shows only a limited injection level dependence, similar to what is observed for silicon carbide, amorphous silicon, and silicon nitride on low resistivity n-type crystalline silicon.…”
Section: A Surface Passivation By Sio 2 Filmsmentioning
confidence: 95%
“…The effective surface recombination velocity on the commonly used p-type c-Si substrates with a resistivity of 1 ⍀ cm was only in the range of 700 cm/ s. 11 Leguit et al and Sivoththaman et al were able to reach minimal effective surface recombination velocities of ϳ100 cm/ s on moderately doped p-or n-type c-Si. 12,13 However, for higher doping levels the effective surface recombination velocity strongly increases. 12,13 It should be noted that the surface passivation of the as-deposited SiO 2 films in all these studies was rather poor and a 20 min or 15 h anneal at 350-400°C in a forming gas ͑commonly 10% H 2 in nitrogen͒ was required to achieve the reported level of surface passivation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations